The key residue responsible for the red shift of bioluminescence spectra of light-sensitive Ca2+-regulated photoproteins of ctenophores - Ludmila P. Burakova; Eugene S. Vysotski (Scientific Reports)
Abstract Isoforms of some ctenophore photoproteins show different maxima of bioluminescence spectra— the ones of mnemiopsin and bolinopsin have λmax at 490 and 500 nm, while λmax for velamin isoforms are at 500 and 508 nm. The reasons for the fact have not yet been established. Here we report on the construction and characterization of a set of mutants of berovin from ctenophore Beroe abyssicola with a substitution of Ala in position 106, which was selected for mutagenesis based on the comparison of the amino acid sequences of ctenophore photoproteins and the spatial structure model of berovin, to the residues with different properties of their side chains. The appearance of only Ser in this position, and its OH group in particular, is demonstrated to result in a green light emission. Moreover, we propose a plausible mechanism of bioluminescence spectrum shift towards longer wavelengths and the function of certain residues situated near OH group of the 6-(p-hydroxy)-phenyl substituent of coelenterazine in this process. We also conclude that the suggested mechanism of emitter formation is valid for other ctenophore photoproteins as well.